Field Notes on Democracy : Listening to Grasshoppers - Roy, Arundhati (Lahore Services Book Club, 2011)
Collects essays exploring democracy in modern India, looking at how religious majoritarianism, cultural nationalism, and neo-fascism are threatening freedom in the world's largest democracy.
Include Index
Keywords: Politics and government -- Democracy -- Social conditions